Glass ceramic material, plug core and preparation method of plug core
By using glass ceramic materials and multi-step process processing, a core blocking with high brittleness and uniform small particle fragments was prepared, which solved the problems of insufficient crushing properties of existing blocking devices and sharp corners, and achieved the effects of high clogging strength and good safety performance.
Patent Information
- Application Number
- CN202311369534.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
In existing oil and gas well pressure operations, the blocker is insufficient in crushing and sharp corners of the debris, resulting in safety hazards and pipeline damage risks.
Using glass ceramic materials, the plug core with high brittleness and uniform small particle fragments was prepared by adjusting the mass ratio of Li2O and Al2O3 and undergoing melting, crystal heating, chemical strengthening and physical strengthening treatment.
It achieves the effect of high clogging strength, thorough crushing and no sharp corners, ensuring the full diameter and safety performance of the oil pipe, and avoiding the risk of pipe scratches.
Smart Images

Figure CN119859022A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of oil and gas well downhole operation with pressure, and in particular to a glass ceramic material, a plugging core and a preparation method thereof. Background Art
[0002] With the development of oil and gas fields, pressure operation, as an advanced downhole operation technology, can minimize the pollution to the formation, protect the reservoir, is safe, environmentally friendly and low-cost, and has been promoted and applied in many oil and gas fields. In order to prevent the fluid in the well from entering the oil pipe, a plugging tool in the oil pipe must be used. The soluble plugs and cast iron plugs currently used have the problem that the plugs are insoluble or dissolved after the well is completed, causing foreign matter to block the pipe column and affect the continuous drainage or production of the gas well.
[0003] Alumina ceramics are used to prepare plugging cores due to their high strength and high brittleness. However, alumina ceramic plugs that are broken more thoroughly are all imported. When alumina arc rupture disks are used as plugging core tools, there is a risk of scratching the pipeline due to the relatively large positive breaking pressure and the large sharp corners of the fragments after breaking.
[0004] Therefore, there is an urgent need for a safe material that can meet the plugging strength requirements, break thoroughly, have high brittleness, and break without sharp corners, so as to meet the requirements of crushing type plugs in oil and gas development. Summary of the invention
[0005] In view of the problems in the prior art of low plugging strength and great safety hazards caused by sharp-angled fragments, the present invention provides a glass ceramic plugging material, a plugging core and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention provides a glass ceramic material, which comprises the following raw material components in molar percentage: 6% to 15% of Li2O, 60% to 75% of SiO2, 6% to 12% of Al2O3, 0% to 1% of K2O, 1% to 3% of Na2O, 1% to 3% of P2O5, 0% to 1% of ZrO2, 0% to 2% of CaO and 0% to 3% of CeO2.
[0008] The present invention provides a plugging core, which is prepared by using the above-mentioned glass ceramic material.
[0009] Preferably, the crystal content of the plugging core is 40% to 55%.
[0010] The present invention also provides a method for preparing the plugging core as described above, comprising the following steps:
[0011] Weigh the raw materials according to the molar percentage of the raw material components of the glass ceramic material;
[0012] The weighed raw materials are mixed and melted to obtain slurry;
[0013] The molten slurry is cast and formed according to the requirements of the plugging core, and annealed and polished to obtain the glass plugging core;
[0014] The glass plugging core is subjected to a crystallization heat treatment to obtain a prefabricated micro-ceramic glass plugging core;
[0015] The prefabricated microcrystalline glass plugging core is chemically and physically strengthened to obtain the plugging core.
[0016] Preferably, the melting temperature is 1400° C. to 1600° C., and the melting time is 2 to 4 hours.
[0017] Preferably, the annealing temperature is 450° C. to 550° C., and the annealing time is 1.5 to 2.5 hours.
[0018] Preferably, the conditions for the crystallization thermal treatment are 700° C. to 850° C., and the holding time is 15 to 120 minutes.
[0019] Furthermore, the method of chemical strengthening is: immersing the prefabricated microcrystalline glass plug into molten salt, heating it to perform ion exchange, and completing chemical strengthening.
[0020] Preferably, the molten salt is KNO3 with KOH added, the amount of KOH added to the molten salt is 1wt% to 5wt%, the heating temperature is 400°C to 800°C, and the ion exchange time is 1 to 5h.
[0021] Preferably, the physical strengthening conditions are: strengthening temperature is 730° C. to 800° C., and strengthening time is 80 to 180 seconds.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention discloses a glass ceramic material, which comprises the following raw material components in terms of molar percentage: 6% to 15% Li2O, 60% to 75% SiO2, 6% to 12% Al2O3, 0% to 1% K2O, 1% to 3% Na2O, 1% to 3% P2O5, 0% to 1% ZrO2, 0% to 2% CaO and 0% to 3% CeO2. The material has an extremely low expansion coefficient or even a zero expansion coefficient within its application temperature range, and is suitable for preparing plugging tool plugging materials. By adjusting the mass ratio of Al2O3 and Li2O in the raw material components and crystallizing through controlled heat treatment, two crystals of Li2Si2O5 and β-spodumene can be precipitated simultaneously, wherein the β-spodumene crystals are equiaxed grains, and the microcrystalline glass containing β-spodumene usually has low thermal expansion and excellent chemical durability, but poor mechanical properties, and the microcrystalline glass containing Li2Si2O5 crystals can have a bending strength as high as 550MPa or more. It can effectively make up for the poor mechanical properties of microcrystalline glass containing β-spodumene. This material combines the excellent mechanical properties of Li2Si2O5 microcrystalline glass with the excellent thermal expansion properties of microcrystalline glass containing β-spodumene crystals, which meets the performance of plugging tools in downhole oil pipes while ensuring dimensional accuracy. Moreover, due to the high glass phase content and high brittleness, this material is extremely easy to break compared with alumina ceramic materials. The fragments after positive crushing are uniform small particles and have no sharp corners, which effectively ensures the full diameter of the oil pipe while avoiding the risk of scratching the pipe, and has high safety performance.
[0024] The present invention provides a plug, which is prepared using the above-mentioned glass ceramic material. The plug can avoid the dimensional influence caused by temperature changes, and the characteristic that the compression strength of brittle materials is much greater than the tensile strength, so as to achieve high pressure bearing capacity at the lower end and low pressure bearing capacity at the upper end, so as to ensure safety and reliability during operation. After the pressure operation is completed, the rupture disk is broken by pressing and other methods to achieve oil casing connection. The plug combines the excellent mechanical properties of Li2Si2O5 microcrystalline glass and the excellent thermal expansion properties of β-spodumene microcrystalline glass, which not only ensures the mechanical properties of the material in the preparation of plug cores, but also has the characteristics of high brittleness and easy crushing, and the fragments are uniform and fine particles without sharp corners, so as to effectively ensure the full diameter of the oil pipe while avoiding the risk of scratching the pipe.
[0025] The crystal phase content of the plugging core is 40% to 55%, which can effectively ensure excellent thermal expansion performance while meeting the mechanical properties of the plugging core.
[0026] The present invention also provides a method for preparing the above plugging core, which comprises weighing raw materials according to the molar percentage of raw material components; mixing the weighed raw materials and melting them to obtain slurry; casting and molding the slurry according to the requirements of the plugging core, annealing and polishing to obtain a glass plugging core; performing crystallization heat treatment on the glass plugging core to obtain a prefabricated microcrystalline glass plugging core; chemically strengthening and physically strengthening the prefabricated microcrystalline glass plugging core to obtain the plugging core. The plugging core is obtained by a melting method, and through crystallization heat treatment, chemical strengthening and physical strengthening, the mechanical properties of the plugging core are improved while maintaining the intrinsic brittleness of the glass, making it easy to break, and the fragments are in the form of fine particles without sharp corners, which is reliable and highly safe. The preparation method is simple and easy to operate, and is suitable for industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a schematic flow chart of a method for preparing a glass ceramic plugging core. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0029] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0031] In the description of the embodiments of the present invention, it should be noted that if the terms "upper", "lower", "horizontal", "inner", etc. indicate an orientation or positional relationship based on the orientation or positional relationship shown in the drawings, or the orientation or positional relationship in which the product of the invention is usually placed when in use, it is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, the terms "first", "second", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.
[0032] In addition, if the term "horizontal" appears, it does not mean that the component must be absolutely horizontal, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", which does not mean that the structure must be completely horizontal, but can be slightly tilted.
[0033] In the description of the embodiments of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0034] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0035] The invention discloses a glass ceramic material, which comprises the following raw material components in molar percentage: 6%-15% of Li2O, 60%-75% of SiO2, 6%-12% of Al2O3, 0-1% of K2O, 1%-3% of Na2O, 1%-3% of P2O5, 0-1% of ZrO2, 0-2% of CaO and 0-3% of CeO2.
[0036] The present invention also provides a plugging core, which is made of the above-mentioned glass ceramic material, and the crystal content of the plugging core is 40% to 55%. Preferably, the thickness of the plugging core is 3 to 5.5 mm;
[0037] See also Figure 1 The present invention also provides a method for preparing the plugging core as described above, characterized in that it comprises the following steps:
[0038] S1: Weigh the raw materials according to the molar percentage of the raw material components of the glass ceramic material;
[0039] S2: mixing the weighed raw materials and melting them to obtain slurry; wherein the melting temperature is 1400° C. to 1600° C. and the melting time is 2 to 4 hours;
[0040] S3: Cast the molten slurry into shape according to the requirements of the plugging core, and anneal and polish it to obtain a glass plugging core; wherein the annealing temperature is 450°C to 550°C, and the annealing time is 1.5 to 2.5 hours
[0041] S4: performing a crystallization heat treatment on the glass plug to obtain a prefabricated microcrystalline glass plug; wherein the crystallization heat treatment condition is 700° C. to 850° C., and the heat preservation time is 15 to 120 minutes;
[0042] S5: chemically and physically strengthen the prefabricated microcrystalline glass plug to obtain the plug. The chemical strengthening method is as follows: immersing the prefabricated microcrystalline glass plug in molten salt, heating at 400°C to 800°C for 80 to 180s to perform ion exchange, wherein the molten salt is KNO3 with KOH added, and the amount of KOH added to the molten salt is 1wt% to 5wt%; the physical strengthening conditions are as follows: the strengthening temperature is 730°C to 800°C, and the strengthening time is 80 to 180s.
[0043] Example 1
[0044] According to the molar percentage, 6% Li2O, 75% SiO2, 6% Al2O3, 1% K2O, 3% Na2O, 3% P2O5, 1% ZrO2, 2% CaO and 3% CeO2 are weighed as raw materials, mixed evenly and melted at 1500°C for 3 hours to obtain slurry; then, the slurry is cast into shape, annealed at 500°C for 2 hours, and polished to obtain an arc-shaped glass plug;
[0045] The glass plugging core is subjected to a crystallization heat treatment, i.e., the glass plugging core is subjected to a heat treatment and crystallization, and the heat treatment condition is 700° C. and maintained at 120 minutes to obtain a prefabricated microcrystalline glass plugging core having a crystal phase content of 55%;
[0046] The prefabricated microcrystalline glass plug is chemically strengthened by placing the prefabricated microcrystalline glass plug in molten KNO3 with KOH added. + and K + Exchange occurs, and the chemical strengthening conditions are that the addition amount of KOH is 1wt%, the temperature is 400℃, and the ion exchange time is 5h; then physical strengthening is carried out, and the prefabricated microcrystalline glass plug after chemical strengthening is physically strengthened under the conditions: temperature is 730℃, and for the microcrystalline glass plug with a thickness of 5.5mm, the strengthening time is 180s.
[0047] After testing, it was found that the plugging core of the oil pipe plugging tool obtained was 5.5mm thick, could withstand a reverse pressure of 80MPa, had a forward crushing pressure of 12MPa, was temperature-resistant above 120°C, had good sealing performance, and the fragments formed after forward crushing were fine particles without sharp corners, ensuring the full diameter of the gas well oil pipe.
[0048] Example 2
[0049] According to the molar percentage, 15% of Li2O, 60% of SiO2, 12% of Al2O3, 1% of K2O, 3% of Na2O, 3% of P2O5, 1% of ZrO2, 2% of CaO and 3% of CeO2 are weighed as raw materials, mixed evenly and melted at 1500°C for 3 hours to obtain slurry; then, the slurry is cast into shape, annealed at 500°C for 2 hours, and polished to obtain an arc-shaped glass plug;
[0050] The glass plugging core is subjected to a crystallization heat treatment, i.e., the glass plugging core is subjected to a heat treatment and crystallization, and the heat treatment condition is 720° C. and maintained for 90 minutes, to obtain a prefabricated microcrystalline glass plugging core having a crystal phase content of 52%;
[0051] The prefabricated microcrystalline glass plug is chemically strengthened by placing the prefabricated microcrystalline glass plug in molten KNO3 with KOH added. + and K + Exchange occurs, and the chemical strengthening conditions are as follows: the addition amount of KOH is 2wt%, the temperature is 420℃, and the ion exchange time is 4h; then physical strengthening is carried out, and the prefabricated microcrystalline glass plug after chemical strengthening is physically strengthened under the following conditions: the temperature is 750℃, and for the microcrystalline glass plug with a thickness of 4mm, the strengthening time is 120s.
[0052] After testing, it was found that the plugging core of the oil pipe plugging tool obtained was 4mm thick, could withstand a reverse pressure of 65MPa, had a forward crushing pressure of 7MPa, was temperature-resistant above 120°C, had good sealing performance, and the fragments formed after forward crushing were fine particles without sharp corners, ensuring the full diameter of the gas well oil pipe.
[0053] Example 3
[0054] According to the molar percentage, 10% of Li2O, 73% of SiO2, 8% of Al2O3, 1% of K2O, 1.5% of Na2O, 1.5% of P2O5, 1% of ZrO2, 1.5% of CaO and 2.5% of CeO2 are weighed as raw materials, mixed evenly and melted at 1500°C for 3 hours to obtain slurry; then, the slurry is cast into shape, annealed at 500°C for 2 hours, and polished to obtain an arc-shaped glass plug;
[0055] The glass plugging core is subjected to a crystallization heat treatment, i.e., the glass plugging core is subjected to a heat treatment and crystallization, and the heat treatment condition is 750° C. and maintained at a temperature for 60 minutes, to obtain a prefabricated microcrystalline glass plugging core having a crystal phase content of 50%;
[0056] The prefabricated microcrystalline glass plug is chemically strengthened by placing the prefabricated microcrystalline glass plug in molten KNO3 with KOH added. + and K +Exchange occurs, and the chemical strengthening conditions are as follows: the addition amount of KOH is 3wt%, the temperature is 440℃, and the ion exchange time is 3h; then physical strengthening is carried out, and the prefabricated microcrystalline glass plug after chemical strengthening is physically strengthened under the following conditions: the temperature is 760℃, and for the microcrystalline glass plug with a thickness of 4.5mm, the strengthening time is 150s.
[0057] After testing, it was found that the plugging core of the oil pipe plugging tool was 4.5mm thick, could withstand a reverse pressure of 70MPa, and a forward crushing pressure of 8MPa. It was temperature-resistant above 120°C and had good sealing properties. The fragments formed after forward crushing were in the form of fine particles without sharp corners, ensuring the full diameter of the gas well oil pipe.
[0058] Example 4
[0059] According to the molar percentage, 12% Li2O, 69% SiO2, 10% Al2O3, 0.5% K2O, 2.5% Na2O, 2% P2O5, 0.5% ZrO2, 1.5% CaO and 2% CeO2 are weighed as raw materials, mixed evenly and melted at 1500°C for 3 hours to obtain slurry; then, the slurry is cast into shape, annealed at 500°C for 2 hours, and polished to obtain an arc-shaped glass plug;
[0060] The glass plugging core is subjected to a crystallization heat treatment, i.e., the glass plugging core is subjected to a heat treatment and crystallization, and the heat treatment condition is 800° C. and maintained at a temperature for 30 minutes, to obtain a prefabricated microcrystalline glass plugging core having a crystal phase content of 48%;
[0061] The prefabricated microcrystalline glass plug is chemically strengthened by placing the prefabricated microcrystalline glass plug in molten KNO3 with KOH added. + and K + Exchange occurs, and the chemical strengthening conditions are as follows: the addition amount of KOH is 4wt%, the temperature is 460℃, and the ion exchange time is 2h; then physical strengthening is carried out, and the prefabricated microcrystalline glass plug after chemical strengthening is physically strengthened under the following conditions: the temperature is 780℃, and for the microcrystalline glass plug with a thickness of 5mm, the strengthening time is 160s.
[0062] After testing, it was found that the plugging core of the oil pipe plugging tool obtained was 5mm thick, could withstand a reverse pressure of 75MPa, had a forward crushing pressure of 10MPa, was temperature-resistant above 120°C, had good sealing performance, and the fragments formed after forward crushing were fine particles without sharp corners, ensuring the full diameter of the gas well oil pipe.
[0063] Example 5
[0064] According to the molar percentage, 15% of Li2O, 73% of SiO2 and 12% of Al2O3 are weighed as raw materials, mixed evenly and melted at 1500°C for 3 hours to obtain slurry; then, the slurry is cast into shape, annealed at 500°C for 2 hours, and polished to obtain an arc-shaped glass plug;
[0065] The glass plugging core is subjected to a crystallization heat treatment, i.e., the glass plugging core is subjected to a heat treatment and crystallization, and the heat treatment condition is 850° C. and kept at a temperature for 15 minutes, to obtain a prefabricated microcrystalline glass plugging core having a crystal phase content of 40%;
[0066] The prefabricated microcrystalline glass plug is chemically strengthened by placing the prefabricated microcrystalline glass plug in molten KNO3 with KOH added. + and K + Exchange occurs, and the chemical strengthening conditions are as follows: the addition amount of KOH is 5wt%, the temperature is 480℃, and the ion exchange time is 1h; then physical strengthening is carried out, and the prefabricated microcrystalline glass plug after chemical strengthening is physically strengthened under the following conditions: the temperature is 800℃, and for the microcrystalline glass plug with a thickness of 3mm, the strengthening time is 80s.
[0067] After testing, it was found that the plugging core of the oil pipe plugging tool obtained was 3mm thick, could withstand a reverse pressure of 60MPa, had a forward crushing pressure of 5MPa, was temperature-resistant above 120°C, had good sealing performance, and the fragments formed after forward crushing were fine particles without sharp corners, ensuring the full diameter of the gas well oil pipe.
[0068] The performance of the foreign ceramic plugging tools provided in Examples 1-5 and the comparative examples was tested for sealing, reverse pressure bearing capacity, forward crushing pressure, etc., all in accordance with GB / T. The results are shown in the following table:
[0069]
[0070]
[0071] It can be seen that the plugging core prepared in the embodiment of the present invention has a reverse pressure bearing capacity level equivalent to or even far superior to that of foreign plugging cores, and its forward crushing pressure is lower than that of the foreign comparative plugging cores. It can be seen that the plugging core prepared in the embodiment of the present invention has the characteristic of being easy to crush in the forward direction.
[0072] In summary, the present invention provides a glass ceramic material, a plug and a preparation method thereof. The material uses a LAS series glass formula as a raw material, and the mass ratio of Al2O3 and Li2O in the raw material is adjusted to obtain an arc-shaped glass plug through melting casting, and then a crystallization heat treatment is performed to control the crystallization to obtain a microcrystalline glass plug, which is then chemically strengthened and physically strengthened in sequence to improve the pressure-bearing performance of the LAS microcrystalline glass plug while maintaining its intrinsic brittleness, making it easy to break, and the fragments are in the form of fine particles without sharp corners, thereby ensuring the full diameter of the oil pipe, providing a reliable physical plugging of the wellbore for the oil pipe under pressure operation, and ensuring operation safety.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.
Claims
1. A glass ceramic material, characterized in that: The raw material components are as follows, measured by mole percentage: 6% to 15% Li2O, 60% to 75% SiO2, 6% to 12% Al2O3, 0% to 1% K2O, 1% to 3% Na2O, 1% to 3% P2O5, 0% to 1% ZrO2, 0% to 2% CaO and 0% to 3% CeO2.
2. A plugging core, characterized in that: The glass ceramic material is prepared using the glass ceramic material according to claim 1.
3. The plugging core according to claim 2, characterized in that: The crystal content of the plugging core is 40% to 55%.
4. The method for preparing the plugging core according to claim 2 or 3, characterized in that: The following steps are involved: Weigh the raw materials according to the molar percentage of the raw material components of the glass ceramic material; The weighed raw materials are mixed and melted to obtain slurry; The slurry is cast and formed according to the requirements of the plugging core, and annealed and polished to obtain the glass plugging core; The glass plugging core is subjected to a crystallization heat treatment to obtain a prefabricated micro-ceramic glass plugging core; The prefabricated microcrystalline glass plugging core is chemically and physically strengthened to obtain the plugging core.
5. The method for preparing the plugging core according to claim 4, characterized in that: The melting temperature is 1400°C to 1600°C, and the melting time is 2 to 4 hours.
6. The method for preparing the plugging core according to claim 4, characterized in that: The annealing temperature is 450°C to 550°C, and the annealing time is 1.5 to 2.5 hours.
7. The method for preparing the plugging core according to claim 4, characterized in that: The conditions for the crystal thermal treatment are 700°C to 850°C, and the holding time is 15 to 120 minutes.
8. The method for preparing the plugging core according to claim 4, characterized in that: The method of chemical strengthening is: immersing the prefabricated microcrystalline glass plug in molten salt, heating it to perform ion exchange, and completing chemical strengthening.
9. The method for preparing the plugging core according to claim 8, characterized in that: The molten salt is KNO3 with KOH added, the amount of KOH added in the molten salt is 1wt% to 5wt%, the heating temperature is 400°C to 800°C, and the ion exchange time is 1 to 5h.
10. The method for preparing the plugging core according to claim 4, characterized in that: The physical strengthening conditions are: strengthening temperature is 730℃~800℃, and strengthening time is 80~180s.